EFEKTIVITAS PEMBERIAN KOMPENSASI FINANSIAL PERUSAHAAN - Meliana, Vina (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
Providing compensation to employees is important for every company, including PT INTI to retain qualified employees today and in the future. PT INTI is a company whose primary based as telecommunication contractor located in Bandung. This study was conducted to determine the effect between direct financial compensation variables and indirect financial compensation toward employee performance. This research uses the descriptive method and data analysis with the path and regression analysis. The result of this research is a descriptive condition of direct and indirect financial compensation in PT INTI in the reality of 2008 is not good based on continuum line where the average percentage is 30,21% where employee expectation to incentive and celebration of the holiday is large. In addition, the simultaneous test shows that there is no linear relationship between direct compensation and indirect compensation for employee performance at PT INTI. Keywords: compensation, employee performance, financial compensation